Research Progress of the Biosynthesis, Abiotic Stress Regulation and Physiological Functions in Plant Polyphenols - Zhenjia TAI; Xinhui WANG; Xuejian SONG; Zhiming LI; Dongjie ZHANG; Zhijiang LI (Shipin gongye ke-ji)
Plant-derived polyphenols belong to a class of secondary metabolites characterized by phenolic hydroxyl structures in plant tissues. Their biosynthesis is mediated by the shikimic acid, phenylpropanoid and flavonoid pathways. The biosynthesis and accumulation of plant polyphenols are influenced by abiotic stress factors. Applying suitable abiotic stress conditions, such as illumination, temperature, salt, and heavy metal ions could enhance the expression and activity levels of polyphenol biosynthetic enzymes, thereby promoting the synthesis and accumulation of polyphenols and resulting in richness of bioactive components. Plant polyphenols exhibit physiological functions, including antioxidant, anti-inflammatory, anticancer, antibacterial, and blood sugar regulation. Firstly, the structure and classification of plant polyphenols are reviewed, along with their biosynthetic pathways and related enzymes; subsequently, the effects of various non-biological stress factors on their biosynthesis are discussed. Finally, their physiological functions and mechanisms of action are summarized, which aims to provide new insights for enriching plant polyphenol resources and enhancing specific functions through non-biological stress methods.